(untitled) (Research, Society and Development, 2020)
The objective of this study was to analyze the scientific production about the application of clinical simulation in children’s emergency services in the nursing undergraduate scenario. For this, an integrative review was developed, through a bibliographic survey carried out between January and April 2017, in the CINAHL, SCOPUS, WEB OF SCIENCE and PUBMED databases, from 2012 to 2016. The descriptors used were: Education Nursing, Emergencies, Patient Simulation, Pediatrics and Teaching. The final sample of the review was composed of three articles, all of them descriptive. 2014 was the year with the highest number of article publications, two publications, most of which were developed in the United States, with the prevalence of the English language. The results suggest that the simulation is able to rescue the operative reasoning in the students during the action, develop critical-reflective thinking about competence and, above all, promotes satisfaction. It is concluded that the strategy enables the development of the competence of evaluation and assistance to the pediatric client in the dimensions of knowledge, doing and wanting to act.